Somatosensory and Biomechanical Abnormalities in Females With Patellofemoral Pain. Issue 10 (October 2016) - Noehren, Brian; Shuping, Logan; Jones, Aron; Akers, David A.; Bush, Heather M.; Sluka, Kathleen A.
Abstract : Objectives: Chronic patellofemoral pain (PFP) is a common orthopedic condition for which little is understood of the alterations in pain processing such as hyperalgesia, hypoesthesia, and the relationship of altered knee mechanics to hyperalgesia. We assessed pain, pressure pain thresholds (PPT), detection to light touch, and the relationship of pain and PPTs to knee abduction angle during a stair step down task between females with and without PFP. Materials and Methods: Twenty females diagnosed with PFP and 20 age-matched pain-free females participated in this study. Individuals underwent an instrumented assessment of knee mechanics during a stair step down task, PPT and detection of light touch over the center of the patella and lateral retinaculum, and PPT outside painful area over the right elbow. Results: The PFP group had significantly lower PPT values at the patella ( P =0.02), lateral retinaculum ( P =0.001), and at the elbow ( P =0.03). There was an elevated threshold to detect light touch over the center of their patella ( P =0.04). A significant relationship between both pain ( r =−0.49, P =0.03) and PPT values ( r =0.65, P =0.004) to the frontal plane knee angle existed in the PFP group which was not present in the control group ( r =−0.17, P =0.49) or in the elbow ( r =−0.009, P =0.972). Discussion: These results suggest that PFP is characterized by an increase in both localized and centralized pain sensitivity that is related to movement mechanics. Thus, PFP has both biomechanical, nociceptive components as well as inferred aspects of altered central sensitization.